Employee performance, well‐being, and differential effects of human resource management subdimensions: Mutual gains or conflicting outcomes?. (24th July 2018) - Ogbonnaya, Chidiebere; Messersmith, Jake
Abstract: The human resource management (HRM) literature supports the idea that coherent systems of HRM practices can induce attitudinal effects when perceived subjectively by employees. Recently, scholars have proposed that subdimensions of HRM systems exist and account for variance in outcomes. This study explores differential effects of three subdimensions of HRM systems (skill‐, motivation‐, and opportunity‐enhancing HRM practices) on employee innovative behaviours and well‐being. Our predictions are based on the mutual gains perspective, which specifies positive relationships between HRM practices and employee performance, and the conflicting outcomes perspective that links HRM practices to higher job demands and stress. Using data from the Finnish 2012 Practices of Working Life Survey, we find support for both the mutual gains and conflicting outcomes perspectives; however, we also show that the effects of the subsets of HRM practices are heterogeneous.